Bru-ha-ha-ha-ha-ha... bru-hi-hi-hi-hi-hi... - Remigio, Ma. Corazon (Adarna karanasan, 1995)
A small girl fears her neighbor, Mrs. Magalit is a witch. She loses her fear when an accident befalls Mrs. Magalit.